2019
DOI: 10.1007/s40333-019-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of water-active soil layer along the south-north transect in the Loess Plateau of China

Abstract: Soil water is an important composition of water recycle in the soil-plant-atmosphere continuum. However, intense water exchange between soil-plant and soil-atmosphere interfaces only occurs in a certain layer of the soil profile. For deep insight into water active layer (WAL, defined as the soil layer with a coefficient of variation in soil water content >10% in a given time domain) in the Loess Plateau of China, we measured soil water content (SWC) in the 0.0-5.0 m soil profile from 86 sampling sites along an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Therefore, the invariable isotope compositions of deep soil 215 water indicate that deep soil water is free of seasonal variation in evaporation and precipitation infiltration (Thomas et al, 2013;Sprenger et al, 2016;Cheng et al, 2014). This is consistent with previous isotope studies (Wan and Liu, 2016;Yang and Fu, 2017) and is supported by the observation of soil water dynamics in this region (Zhao et al, 2019). Moreover, the reduced variations of stable isotopes in deep soils can be attributed to the mixing processes in the deep unsaturated zone since it has the long residence time (DePaolo et al, 2004;Thomas et al, 2013).…”
Section: What Is the Timescale Of Our F Estimates Based On Deep Soil supporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the invariable isotope compositions of deep soil 215 water indicate that deep soil water is free of seasonal variation in evaporation and precipitation infiltration (Thomas et al, 2013;Sprenger et al, 2016;Cheng et al, 2014). This is consistent with previous isotope studies (Wan and Liu, 2016;Yang and Fu, 2017) and is supported by the observation of soil water dynamics in this region (Zhao et al, 2019). Moreover, the reduced variations of stable isotopes in deep soils can be attributed to the mixing processes in the deep unsaturated zone since it has the long residence time (DePaolo et al, 2004;Thomas et al, 2013).…”
Section: What Is the Timescale Of Our F Estimates Based On Deep Soil supporting
confidence: 92%
“…Precipitation and soil evaporation are two main factors to the variation of soil water isotopes; however, soil evaporation is limited to a few to dozens of centimeters only (Cheng et al, 2014) and precipitation infiltration depth rarely exceeds two meters at our study area (Jin et al, 2018;Zhao et al, 2019). Therefore, the invariable isotope compositions of deep soil 215 water indicate that deep soil water is free of seasonal variation in evaporation and precipitation infiltration (Thomas et al, 2013;Sprenger et al, 2016;Cheng et al, 2014).…”
Section: What Is the Timescale Of Our F Estimates Based On Deep Soil mentioning
confidence: 88%
“…Many field experiments have been conducted on the Chinese Loess Plateau to reveal spatial and temporal distributions of soil water (He et al, 2019;Liang et al, 2019;Zhao et al, 2019;Yu et al, 2020), while influences of soil physical properties on SWC were seldomly been studied. Geostatistics have also been used to assess heterogeneity of surface soil water (Zou et al, 2019); however, the analysis of SWC using this method was greatly affected by spatial scale (Lian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the impact of the precipitation on soil hydraulic properties might be reduced. For preferential flow, studies showed that the modern water active layer was no more than 2 m on the Loess Plateau [63], whereas the modern climate of the CLP is wetter than that of the last glacial period, and the impact of water flow on soil pedogenesis is a time consuming process [52]. For the intact and typical paleosol layer, the influence of precipitation on soil hydraulic properties may not have been so severe, and the hydraulic properties of the paleosol were mainly determined by the paleoclimate when it developed.…”
Section: Effects Of Precipitation On Soil Hydraulic Properties After mentioning
confidence: 99%